DEVELOPMENT OF AUTOTROPHIC DENITRIFICATION FOR NITRATE-CONTAMINATED INDUSTRIAL WASTEWATER - Nugroho, Rudi (Center for Environmental Technology, 2007)
An autotrophic denitrification system was developed for treatment wastewater from steel industry. The aim was to evaluate the kinetics and capability of the system in reducing nitrate content in such industrial wastewater. The experiments were conducted in batch suspension and continuous runs. The denitrification kinetics in suspension runs obeys first order reaction with the rate constant k1 and k2 were determined to be 0.014 and 0.004 g-N/m3.d, respectively. The continuous runs used a column packed with mixture of granular sulfur and limestone. The microbes of Thiobacillus denitrificans were attached on the surface of granular sulfur in the form of biofilm. The biofilm thickness was investigated to be approximately 40 ÃŽÂ¼m. The denitrification kinetics in the packed column obeys half-order reaction with the rate constant k of 0.172 g-N1/2.m1/2/(kg-S.d). The lower denitrification extent of industrial wastewater compared with the synthetic wastewater might be due to the lack of alkalinity.Ã‚Â Keywords: Autotrophic denitrification, sulfur, packed column, thiobacillus denitrificans.